Adolescent PCOS and long-term metabolic risk: insights from triglycerides to high-density lipoprotein cholesterol ratio and high-density lipoprotein cholesterol profiles - Nowak-Ciołek, Maria; Stachowiak, Julia Jagoda; Krok, Katarzyna; Sokal, Julia; Malczyk, Żaneta; Skrzyńska, Karolina; Zachurzok, Agnieszka (Frontiers in Endocrinology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is a complex endocrine disorder affecting 6–22% of women worldwide, with adolescent diagnosis posing significant challenges due to physiological differences between adolescents and adults. Historically, the application of the Rotterdam criteria in adolescent girls led to overdiagnosis, prompting the introduction of revised adolescent-specific criteria in 2017. These updated criteria require the presence of both irregular menstrual cycles and hyperandrogenism while excluding criterion of polycystic ovarian morphology. This study aims to assess whether a PCOS diagnosis based on adolescent-specific criteria correlates with an increased risk of metabolic disturbances in adulthood.MethodsA retrospective analysis was conducted on medical records of 34 adolescent patients diagnosed with PCOS according to the Rotterdam criteria, who were divided into a study group (SG, n=23) meeting the updated adolescent PCOS criteria and a comparison group (CG, n=11) that did not meet these criteria. After the mean follow-up of 5.5 years, they were reassessed based on clinical and metabolic parameters. Clinical assessments included body mass index (BMI), Ferriman-Gallwey scale, and body composition analysis. Biochemical analyses involved fasting lipid profiles, glucose metabolism markers, and insulin resistance indices.ResultsApplication of the updated diagnostic criteria resulted in a 33% reduction in PCOS diagnoses among adolescents. No significant differences in BMI were observed between SG and CG on the first and second visits. The triglycerides (TG) to HDL-cholesterol (HDL-C) ratio was significantly higher in the SG across both time points (p=0.029 in adolescence, p=0.049 in adulthood), correlating positively with insulin levels during adolescence (p=0.005, R=0.61). Additionally, HDL-C levels were consistently lower in the SG than in CG (p=0.025 in adolescence, p=0.033 in adulthood).ConclusionThe findings of this study suggest that the revised PCOS criteria in adolescence may assist in identifying individuals at risk of long-term metabolic abnormalities. Elevated TG/HDL-C ratios and persistent HDL-C abnormalities observed in the study group may indicate a metabolic predisposition independent of obesity. These preliminary results emphasize the potential importance of early metabolic monitoring in adolescent PCOS patients; however, they should be interpreted with caution and confirmed in larger cohorts to ensure sufficient statistical power and broader generalizability.